Конфесійний чинник генези козацької автономії в складі Речі Посполитої - Щербак, В. (Чорноморська минувшина, 2017)
У статті проаналізовано основні засади і шляхи формування ідеї козацької автономії в Речі Посполитій наприкінці XVI – першій половині XVII ст. Увага акцентується на ролі православ’я в цьому процесі через спілку oчільників Війська Запорозького та українських духовних ієрархів. The article analyzes the basic principles and ways of forming the idea of Cossack autonomy in the Polish-Lithuanian Commonwealth in the end of the XVI - the first half of the XVII c. Principles of self-government as an important factor of autonomy were created on Zaporozhian Sich. They led to the emergence of political projects in which the leading role was played by the Zaporozhian Army. The Cossacks' struggle for rights and privileges coincided in time with the intensification of the confessional issues in Ukraine. The union of the Cossack elite with the Orthodox hierarchs contributed to the awareness of the positions of both sides in the conditions of Polish expansion. Protection of Orthodoxy occupied an important position in the mottos of their leaders during the Cossack rebellions. At the same time calls for the creation of the Cossack autonomy within the Polish-Lithuanian Commonwealth were increasingly spreading and have been finally established with the unfolding of the Liberation War. В статье анализируются основные принципы и пути формирования идеи казаческой автономии в составе Речи Посполитой в конце XVI – первой половине XVII в. Внимание акцентируется на роли православия в этом процессе на примере союза руководителей Войска Запорожского и украинских духовных иерархов.